FORMATION OF ECOLOGICAL CONSCIOUSNESS IN THE CONTEXT OF GLOBALIZATION - Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Continuous economic development is the cause of consumption increase, which, under the limited natural resources, cannot but lead to catastrophic consequences. This actualizes the study of environmental problems of modern society, especially in the context of man’s awareness of the final results of uncontrolled use of nature. The aim and tasks are aimed at socio-philosophical studying the specificity of the formation of ecological consciousness in the context of globalization. Research methods used in the study are dialectical, comparative and prognostic methods in their integrative combination. Research results. A necessary condition for the preservation of natural diversity and the restoration of the environment in the context of globalization is the formation of ecological social consciousness and morality on fundamentally new principles, values and priorities that meet socio-centric worldview guidance. Ecological consciousness determines the development of the structure and directions of socio-economic development of mankind and influences human behavior, taking into account the real threats from its own actions. Discussion. Ecological consciousness is a set of sensory and imaginary images that are constantly changing and directly record individual or social environmental experience, which involves environmental practice and forecasting. Conclusion. In modern society, environmental problems are the greatest danger to all the humans and their descendants, which determines the leading place of the environmental factor in the system of axiological principles of a globalized society.